A review of the determinants of economic burden among caregivers providing long-term care for the elderly - Hasmat, Nurul Ezam Asri; Mahat, Nur Ain; Aljunid, Syed Mohamed; Che Hasan, Muhammad Kamil; Mustapa Kamal Basha, Muzaitul Akma; Pairoh, Hasanah (Universiti Putra Malaysia, 2025)
Introduction: Caregiving has emerged as a global challenge, and despite this, many young people take on the role of caregiver. The responsibility of providing long-term care can be especially demanding and overwhelming. This review aims to examine the economic burden experienced by caregivers and identify the factors contributing to financial stress in the context of long-term elderly care. Materials and Methods: A complete search was conducted on four databases: PubMed, ScienceDirect, ProQuest, and Scopus. This is to identify studies on caregivers’ strain on elderly long-term care, particularly financial load. A narrative approach was utilised to examine and determine the prevalence of financial stress in long-term care for the elderly in literature. Results: The review found 19 publications that fit the criteria and offered information about the financial challenges that caregivers face. According to the articles evaluated, money played a significant impact in lowering or raising the caregiver load; however, other socio-demographic characteristics, such as education level, age, and location of residence, also contributed to finances. Most articles agree that inpatient expenditures are greater than outpatient costs, with one study reporting RM 3,051 for inpatients and RM 172.68 for outpatients. Conclusion: As medical technology advances in a developing country, the number of elderly people is increasing. While various forms of assistance are provided by government and non-governmental organisations (NGOs), healthcare costs remain high. Further research is needed to help reduce costs and economic burdens for the elderly, ensuring they can fully benefit from available healthcare services.